Infections and Sepsis Development - Neri, Vincenzo; Huang, Lixing; Li, Jie (IntechOpen, 2021)
Infection is a common clinical condition that may cause local inflammation but, in some cases, can lead to systemic inflammation, with sepsis and organ dysfunction. Septic shock is a condition of inadequate tissue perfusion and cellular use of oxygen due to the cytotoxic action of bacterial toxins. There is no relationship between the pathological characteristics and the severity of the primary septic outbreak and the development of septic shock, and the time that elapses until the start of the shock is not predictable. Thus, knowledge of the pathophysiology of septic shock is fundamental for treatment. This book presents a comprehensive overview of infectious agents and their therapeutic control, pathological conditions with infective etiology such as diabetic foot osteomyelitis and infections in neurosurgery, and the pathophysiology, diagnosis, and management of sepsis.